Dynamic multiprocessor scheduling model for the reconfigurable mesh computing networks [UTM journal article] - Shaharuddin Salleh; Nur Arina Bazilah Aziz; Nor Afzalina Azmee; Nurul Huda Mohamed
PSZJBL